AN ASSESSMENT OF THE SOCIAL PROTECTION PROJECT: THE GAMBIA SOCIAL SAFETY NET PROGRAMMES AND THE STANDARD OF LIVING IN THE COUNTRY - FAYE, NJAMMEH; OBAH-AKPOWOGHAHA , NELSON GOLDPIN (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2023)
The study evaluated the impact of the Gambia's social safety net programmes on the country's standard of living. The goal is to identify the basic roles of the Gambia Social Safety Net Programme (TGSSNP) on the standard of living in The Gambia, examine the impact of TGSSNP on the standard of living of beneficiaries in The Gambia, and assess the challenges that TGSSNP faces in improving the standard of living of beneficiaries in the country. The research used questionnaire in the study. The snowball sampling approach and purposive sampling were used in the study. The snowball was used to connect the researcher with other beneficiaries from one point of contact to the next. However, for the quantitative data, 398 respondents were purposively chosen for the study, but for the qualitative data, all members of the social safety nets within the scope of the study were interviewed. The study's findings revealed that, despite the multiple problems that safety net programmes face, their impact on the lives of vulnerable Gambians has been relatively good as it relates to cash transfers, scholarships, assistance on food items, and so on. Although some respondents denied receiving any form of benefit from the program as aforementioned. This confirmed the challenges that social safety net programmes continue to face in areas such as funding and management problem. The study recommended, among other things, that there is a need for more support from investors, the government of the day, and partnerships with agencies on social protection.